A multi-modal visual emotion recognition method to instantiate an ontology - Heredia J.P.A. (2021)
This research was supported by the FONDO NA-CIONAL DE DESARROLLO CIENT´FICO, TEC-NOLÓGICO Y DE INNOVACIÓN TECNOLÓGICA -FONDECYT as executing entity of CONCYTEC under grant agreement no. 01-2019-FONDECYT-BM-INC.INV in the project RUTAS: Robots for Urban Tourism, Autonomous and Semantic web based.